Designing with Light: Advanced 2D, 3D, and 4D Materials. Issue 18 (1st December 2019) - Jung, Kenward; Corrigan, Nathaniel; Ciftci, Mustafa; Xu, Jiangtao; Seo, Soyoung E.; Hawker, Craig J.; Boyer, Cyrille
Abstract: Recent achievements and future opportunities for the design of 2D, 3D, and 4D materials using photochemical reactions are summarized. Light is an attractive stimulus for material design due to its outstanding spatiotemporal control, and its ability to mediate rapid polymerization under moderate reaction temperatures. These features have been significantly enhanced by major advances in light generation/manipulation with light‐emitting diodes and optical fiber technologies which now allows for a broad range of cost‐effective fabrication protocols. This combination is driving the preparation of sophisticated 2D, 3D, and 4D materials at the nano‐, micro‐, and macrosize scales. Looking ahead, future challenges and opportunities that will significantly impact the field and help shape the future of light as a versatile and tunable design tool are highlighted. Abstract : Light is a powerful stimulus, providing easy access to spatiotemporal control, and has been widely employed for material design. As such, photochemical methods empower the fabrication of sophisticated 2D, 3D, and 4D materials at lengths ranging from nano‐ to macroscale.